Women in Alternative Finance Exploring the Benefits of Equity Crowdfunding - Battaglia, Francesca; Giusi Gaeta, Emanuela (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
XIII, 109 p. 16 illus., 15 illus. in color.